The behavior of cells during the evaluation of gap junctional intercellular communication by metabolic cooperation assay - Vítek, J A (Neoplasma, 1996)
The behavior of cells during the assessment of gap junctional intercellular communication (GJIC) by metabolic cooperation assay was studied, either under standard conditions, or with the simultaneous addition of an inhibitor of GJIC-ethylene glycol, and eventually plus dibutyryl cyclic adenosine monophosphate. Generally, the behavior of cells in the course of the assay did not depend significantly on the combination of drugs used. Cell locomotion during the assay was minimal, and consequently the results depended, almost solely on the probability of mutual contact between donor and recipient cells during the seeding. The first significant decrease in recovery of recipient cells, that is a detectable GJIC, was observed 30 min after the assay had started. Final results of the assay depended on the first 12 h of the experiment, in which the maximum decrease in the recovery of recipient cells, that is the maximum GJIC, was reached. The longer duration of the assay did not affect the results significantly.
Keywords: mezibuněčná komunikace; křečci praví; mezerový spoj; Antimetabolites, Antineoplastic; mitóza; zvířata; dibutyryl cyklický AMP; Cell Communication; Bucladesine; Cricetulus; buněčné linie; thioguanin; Ethylene Glycol; Cell Line; protinádorové antimetabolity; Mitosis; Cricetinae; Gap Junctions; fibroblasty; Animals; Ethylene Glycols; ethylenglykoly; Thioguanine; Fibroblasts; ethylenglykol